IMPLIKASI TERBITNYA UNDANG –UNDANG NOMOR 23 TAHUN 2014 TERHADAP SUMBER DAYA MANUSIA PADA UPTD KESATUAN PENGELOLAAN HUTAN PRODUKSI GEDONG WANI PROVINSI LAMPUNG - Andri Kurniawan; Christine Wulandari; Indra Gumay Febryano; Hari Kaskoyo; Sugeng Prayitno Harianto; Agus Setiawan (Jurnal Hutan Tropis, 2021)
The success of managing the forest management unit cannot be separated from the availability of human resources.  The purpose of this study is to study the implications of the issuance of Law Number 23 of 2014 concerning Regional Government on Human Resources in the Gedong Wani Production Forest Management Unit. Data obtained through interviews and library studio analyzed descriptively qualitative.  The results showed that there have been changes in human resources in the Regional Technical Implementation Unit (UPTD) KPHP Gedong Wani.  In addition, there are also several inhibiting and supporting factors in its application. The most important implication is an increase in human resources both in quantity and quality due to the transfer of authory from the center to the regions.  Education and training are still needed to guarantee and improve the quality of human resources in the UPTD KPHP Gedong Wani.